Design, Implementation and Evaluation of a Fault Detection and Emergency Control Strategy for a Quadcopter System - Fredlund,Björn (2024)
In this thesis, a fault detection and diagnosis system is developed for the Crazyflie 2.1 unmanned aerial vehicle. Different types of faults are investigated and suitable methods and tests are implemented. The system is mainly developed for the lighthouse positioning, but the tests and methods are generic and suitable for other parts of the Crazyflie eco-system. For the faults investigated, different methods of bringing the quadcopter to a landed state are explored. To keep user customizability high, different default actions are available to specify for each type of fault. The different actions are implemented as an extension of the onboard state machine and will cause the Crazyflie to respond to a fault in a certain way. The results indicate promising results for the developed control strategy but, because of simplicity, already implemented strategies are preferred. Overall, the implementation is simple, flexible and robust. Additionally, a propeller unbalance estimator developed in previous work was implemented and evaluated. The estimator is able to identify the damaged propeller and estimate the unbalance within the correct order of magnitude. It was, however, deemed too model dependent and thus not suitable as a general service indicator across different Crazyflie setups and configurations.